1994
DOI: 10.1007/bf00348203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highly selective vagotomy and additional procedures on gastric emptying in patients with obstructing duodenal ulcer

Abstract: A solid gastric emptying study was conducted on 46 patients more than 1 year after highly selective vagotomy (HSV) and additional procedures for obstructing duodenal ulcer and on 21 patients after HSV alone for uncomplicated duodenal ulcer. The additional procedures included dilatation (n = 14; HSV + D group), Holle pyloroplasty (n = 14; HSV + P group), and Jaboulay gastroduodenostomy (n = 18; HSV + GD group). The test meal consisted of two eggs labeled with 99mTc sulfur colloid, two slices of white bread toas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[28][29][30][31][32][33][34] In contrast, studies have shown that parietal cell vagotomy or highly selective vagotomy during Nissen fundoplication is not associated with increased side effects, morbidity, or mortality. [35][36][37] It may be that the difference in outcome may be attributed to the underlying disease rather than to the vagotomy.…”
Section: The Short Esophagusmentioning
confidence: 97%
“…[28][29][30][31][32][33][34] In contrast, studies have shown that parietal cell vagotomy or highly selective vagotomy during Nissen fundoplication is not associated with increased side effects, morbidity, or mortality. [35][36][37] It may be that the difference in outcome may be attributed to the underlying disease rather than to the vagotomy.…”
Section: The Short Esophagusmentioning
confidence: 97%
“…Medical management of peptic ulcer has limited its complications and decreased the need for surgical treatment. Surgery (either by resective or non-resective gastric procedures) may be the treatment of choice in selected patients with complications of peptic ulcer 2 3…”
Section: Discussionmentioning
confidence: 99%
“…The gastric emptying study was performed using a method we have previously described and validated 5 . After overnight fasting, a solid‐phase gastric emptying study was performed after subjects consumed a standard test meal with two 99m Tc S‐colloid (54 MBq) radiolabeled eggs, two slices of white bread, and 300 mL of diluted orange juice.…”
Section: Methodsmentioning
confidence: 99%